Two species of Talorchestia Dana 1853 (Crustacea, Amphipoda, Talitridae) including T. lakshadweepensis sp. nov. from the Lakshadweep Islands, India - Trivedi, Jigneshkumar N.; Lowry, James K.; Myers, Alan A.; Keloth, Rajmohana (Zootaxa, 2020)
Two species of the beach-hopper genus Talorchestia Dana, 1853 were collected at Cheriyam Island in the union territory of Lakshadweep in south western India. One species was identified as T. affinis Maccagno, 1936, known previously from the Red Sea, Somalia and East Africa and recorded for the first time from India, the other proved to be a new species, T. lakshadweepensis sp. nov.